Perbedaan Pengaruh Latihan Rope Skipping Dan Quadrant Jump Terhadap Kelincahan Di Persatuan Bulutangkis Tanker Kartasura - SYAUQI, SILMA ROQI ALFIS, Agus Widodo SST.FT, M.Fis (2017)
Background: Agility very needed in badminton players, so that players are able to move and react quickly, accurately, without ever losing his balance and awareness of body position and reach every corner of the field to attempt to recover the shuttle to the game opponents during matches. Objective: To determine the differences in the effects of exercise and Quadrant Jump Rope Skipping on agility in Badminton Association of Tanker Kartasura. Methods: This study is a quasi experimental approaches and methods of two group pre and post test. Samples of this study were 20 people who were divided into two group that is Quadrant Jump group and Rope Skipping group. The study was conducted over 4 weeks, the frequency of exercise 3 times a week. Measurements of agility using Illinois Agility Run Test. Data analysis using Wilcoxon test and Mann-Whitney test. Result : Based on the statistical results to test the effect before and after practice Quadrant Jump obtained p-value 0.005. Quadrant Jump obtained p-value of 0.005, while for the test before and after exercise influence Skipping Rope obtained p-value 0.005 It can be concluded that there is the effect of exercise and Rope skipping Quadrant Jump to agility. To test the effect difference was obtained p-value 0.545, so it can be concluded that there is no difference in the effect of Quadrant and Rope Skipping Jump to agility.